Public Participation in Needs Identification and Prioritization at Local Level Annual Plan: Experiences from Kirtipur Municipality, Kathmandu - Sapkota, Bhaba Datta; Adhikaree, Siddhi Binod (Janabhawana Research Journal, 2023)
The aim of this paper was to examine the preferences of people in needs identification at the ward level annual plan, and to enable the participants in the ward level planning process. The focus area of the study was Kirtipur Municipality ward no 8. The research followed a qualitative method characterized by workshops and mock session methods considering the constructivist standpoint. The words form of data was converted into tabulated form and interpreted accordingly. More than 100 stakeholders participated in the three days long workshops and mock sessions continuously for primary data. As per the policy provision, community people have no access in ordering except needs/programs identification is considered as big policy deficiency. This study found that all the decisive roles have been done by the government officials and hired consultants. The findings of this research suggest that community people’s voices and, more intensively, their ideas must be incorporated while setting the priority orders by training and awareness. The findings suggest that political representatives and government officials must enhance their personal and institutional capacity in relation to understanding the overall planning process. To address the existing policy deficiency, people's participation in every stage of planning is the best way of sustainability in planning and becomes the good benchmarks for theoretical and applied contribution.